Virus-like particle formation of Drosophila copia through autocatalytic processing. - Yoshioka, K.; Honma, H.; Zushi, M.; Kondo, S.; Togashi, S.; Miyake, T.; Shiba, T. (The EMBO Journal, 1990)
Northern blot and nucleotide sequence analyses of copia RNA from a transfectant made by introducing a genomic copia into copia-free cells showed that the 2 kb RNA, one of the major transcripts of copia, is generated through splicing. Using the polymerase chain reaction (PCR), we have also found that the position of the splice sites used in Drosophila larvae and cultured cells originally containing copia is the same as that used in the transfectant. To investigate the function of the 2 kb RNA, we constructed mutant copias which harboured a single point mutation at the splice site or approximately 3 kb deletion of the internal region corresponding to the spliced out sequence. Analyses of transfectants made by introducing these mutant copias into copia-free cells demonstrated that the spliced 2 kb RNA contains sufficient information to make copia virus-like particles (VLPs). Furthermore, when copia RNA corresponding to the spliced RNA was translated in vitro, the major VLP protein was found to be released autocatalytically from its own precursor. A single amino acid substitution at the putative protease active site in the precursor prevented the processing, and resulted in accumulation of the mutant precursor in vitro. From these results, we conclude that copia VLPs are produced through autocatalytic processing of the precursor polyprotein encoded by the spliced copia RNA.